Mannich bases derived from melamine, formaldehyde alkanoleamines as novel corrosion inhibitors for mild steel in hydrochloric acid medium - Verma C.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
The corrosion inhibition of mild steel using two new Mannich bases namely 2,2',2''((((1,3,5-triazine-2,4,6-triyl)tris(azanediyl)tris(Methylene)tris(azanediyl)triethanol (INH-1) and 2,2',2'',2''',2''''((((1,3,5-triazine-2,4,6-triyl)tris(azanediyl)tris(Methylene)tris(azanediyl)hexaethanol (INH-2) has been investigated using weight loss and electrochemical methods . The INH-1and INH-2 showed maximum efficiency of 92% and 95% at 25ppm concentration respectively. Potentiodynamic polarization suggests that the inhibitors depict mixed type behavior. The Electrochemical impedance spectroscopy (EIS) measurement shows that inhibitors were adsorbed at mild steel surface and obeyed Langmuir adsorption isotherm. Various thermodynamic parameters were also determined to investigate the mechanism of corrosion inhibition. The results obtained from weight loss and electrochemical methods are in good agreements. © 2013 by ESG.